The MitraClip Asia‐Pacific registry: Differences in outcomes between functional and degenerative mitral regurgitation. Issue 7 (28th October 2015) - Tay, Edgar; Muda, Nasir; Yap, Jonathan; Muller, David W.M.; Santoso, Teguh; Walters, Darren L.; Liu, Xianbao; Yamen, Eric; Jansz, Paul; Yip, James; Zambahari, Robaayah; Passage, Jurgen; et al.
Abstract : Objectives: The objective of this study is to describe and compare the use of the MitraClip therapy in mitral regurgitation (MR) patients with degenerative MR (DMR) and functional MR (FMR). Introduction: Percutaneous edge‐to‐edge repair of severe MR using the MitraClip device is approved for use in the USA for high risk DMR while European guidelines include its use in FMR patients as well. Methods: TheM itraClip in theA sia‐PacificR egis try (MARS) is a multicenter retrospective registry, involving eight sites in five Asia‐Pacific countries. Clinical and echocardiographic characteristics, procedural outcomes and 1‐month outcomes [death and major adverse events (MAE)] were compared between FMR and DMR patients treated with the MitraClip. Results: A total of 163 patients were included from 2011 to 2014. The acute procedural success rates for FMR (95.5%, n = 84) and DMR (92%, n = 69) were similar ( P = 0.515). 45% of FMR had ≥2 clips inserted compared to 60% of those with DMR ( P = 0.064).The 30‐day mortality rate for FMR and DMR was similar at 4.5% and 6.7% respectively ( P = 0.555). The 30‐day MAE rate was 9.2% for FMR and 14.7% for DMR ( P = 0.281). Both FMR and DMR patients had significant improvements in the severity of MR and NYHA class after 30 days. There was a significantly greater reduction in left ventricular end‐diastolic diameter ( P = 0.002) and end systolic diameter ( P = 0.017) in DMR than in FMR. Conclusions: The MitraClip therapy is a safe and efficacious treatment option for both FMR and DMR. Although, there is a significantly greater reduction in LV volumes in DMR, patients in both groups report clinical benefit with improvement in functional class. © 2015 Wiley Periodicals, Inc.